Associations of Lifetime Trauma and Chronic Stress With C-reactive Protein in Adults Ages 50 Years and Older: Examining the Moderating Role of Perceived Control. Issue 6 (July 2017) - Elliot, Ari J.; Mooney, Christopher J.; Infurna, Frank J.; Chapman, Benjamin P.
ABSTRACT: Objective: The aim of the study was to investigate whether high perceived control mitigates systemic inflammatory risk associated with traumatic and chronic stress exposures in older adults. Methods: A sample of community-dwelling adults ages 50 years and older ( N = 4779) was drawn from the Health and Retirement Study. Structural equation models tested interactions of lifetime trauma and chronic stress with mastery and perceived constraints predicting baseline levels and 4-year change in C-reactive protein (CRP). Results: There were significant interactions of lifetime trauma (β = −.058, p = .012) and chronic stress (β = −.069, p = .010) with mastery as related to baseline CRP levels. Both measures were associated with higher CRP at low (β = .102, p = .003; β = .088, p = .015) but not high levels of mastery. In addition, chronic stress interacted with baseline mastery (β = .056, p = .011) and change in mastery (β = −.056, p = .016) to predict 4-year change in CRP. Chronic stress was associated with an increase in CRP at high baseline mastery (β = .071, p = .022) and when mastery decreased during follow-up (β = .088, p = .011). There were no main effects of stress or control variables other than an association of constraints with a larger increase in CRP (β = .062, p = .017). Interactions were minimally attenuated (<15%) upon further adjustment for negative affect, body mass index, smoking, and physical activity. Conclusions: High mastery may protect against elevated systemic inflammation associated with substantial lifetime trauma exposure. Individuals who experience declines in mastery may be most susceptible to increases in inflammation associated with chronic stress. Abstract : Supplemental digital content is available in the text.